Genome-wide identification of the CPK gene family and associated responses to calcium stress in Hemiboea subcapitata - Zhang, Tianya; Dai, Yi; Gao, Dan; Xiang, Xiaoguo; Guo, Chunce; Lu, Shunbao; Zhang, Yanjie (Frontiers in Plant Science, 2026)
Calcium-dependent protein kinase (CPK) gene family, which can be activated directly by Ca2+, plays an important role in Ca2+ signal transduction and stress response and is widely present in green plants. So far, the role of CPK gene family evolution for species in karst area is far from understanding. Hemiboea subcapitata (Gesneriaceae) was used to explore this issue, for its mainly distributing in the karst area of south China. Our results indicated that 32 highly conserved CPK genes identified were distributed across 14 chromosomes in H. subcapitata. Additionally, 10 gene pairs were generated by fragment replication. Subcellular localization analysis revealed that HsCPKs were mainly localized in chloroplasts and cytoplasm. This gene family experienced intron loss events, but its motif structure was highly similar. Phylogenetic analysis showed that the HsCPKs were divided into four subfamilies. Subfamilies I and II were under neutral selection, while subfamilies III and IV were under strongly positive selection. The HsCPKs showed different expressions in three vegetative organs of H. subcapitata. Meanwhile, the expression levels under calcium stress revealed an overall increasing trend for all HsCPKs examined. Cis-acting elements analysis revealed that HsCPKs contained hormone-responsive elements related to stress. The expansion and evolution of CPK gene family in H. subcapitata may be related to its adaptation to calcium-rich and stressed habitats. This study provides a valuable understanding for the roles of the CPK gene family within karst species.